The positive integers m and n leave remainders of 2 and 3, respectively, when divided by 6. m>n. What is the remainder when m–n is divided by 6?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We are given that the numbers m and n, when divided by 6, leave remainders of 2 and 3, respectively.
Hence, we can represent the numbers m and n as 6p+2 and 6q+3, respectively, where p and q are suitable integers.
Now, m–n=(6p+2)–(6q+3)=6p–6q–1=6(p–q)–1.
A remainder must be positive, so let’s add 6 to this expression and compensate by subtracting 6: 6(p–q)–1=6(p–q)–6+6–1=6(p–q)–6+5=6(p–q–1)+5 Thus, the remainder is 5